1984
DOI: 10.1016/s0735-1097(84)80249-1
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic detection of ischemic and infarcted myocardium

Abstract: The purpose of this study was to determine the potential of a clinically adaptable two-dimensional echocardiographic system using computer enhancement and a mathematically defined integrated backscatter ratio for the early detection of ischemic and infarcted myocardium. Fifteen dogs had two-dimensional echocardiograms recorded during either open chest coronary occlusion (n = 5), closed chest occlusion (n = 5), occlusion followed by reperfusion (n = 3) or sham coronary occlusion (n = 2). A serial increase in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Thus, a variable must be free of any angle dependence with respect to the region of interest and free from attenuation effects. An absolute measurement such as mean backscatter power, which has been used by several investigators, 22,23,28,29 has certain reference difficulties that potentially limit its clinical usefulness. On the other hand, relative measurements such as the cyclic backscatter power and the phase relationship may be useful in the clinical environment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a variable must be free of any angle dependence with respect to the region of interest and free from attenuation effects. An absolute measurement such as mean backscatter power, which has been used by several investigators, 22,23,28,29 has certain reference difficulties that potentially limit its clinical usefulness. On the other hand, relative measurements such as the cyclic backscatter power and the phase relationship may be useful in the clinical environment.…”
Section: Discussionmentioning
confidence: 99%
“…Those schemes which rely on cyclic variation in this backscattered intensity [50] are directly linked to the mechanical function of the heart and may not provide additional information above analysis of wall motion alone. Other investigators however have looked at the myocardial intensity at only one point in time, thus in part separating out the effect of wall motion [51][52][53][54][55]. In virtually all studies reported to date there are statistically significant differences in the intensity and quality of backscattered ultrasound in infarcted or ischemic myocardium when compared to normal control regions.…”
Section: Tissue Characterizationmentioning
confidence: 99%
“…The distribution of these intensities is then subject to statistical analysis and a description of their uniformity (or lack of uniformity) is generated. Most studies have demonstrated that with the onset of ischemia overall backscatter intensity increases [51][52][53][54][55] and the range of distribution of the gray levels becomes broader [53]. Fig.…”
Section: Tissue Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, improved methods of gain compensation for attenuation will be required to deal effectively with this problem. Rasmussen et al [27] recently described a method involving the use of an internal myocardial reference calibration which compensates for the backscatter influence of the chest wall, coupled with computer acquisition and enhancement of myocardial images. The further applicability of this method to all myocardial regions remains to be determined.…”
Section: Relationship To Previous Observationsmentioning
confidence: 99%